Assessing and managing stressors in a changing marine environment. Issue 2 (30th November 2017) - Chapman, Peter M
Abstract: We are facing a dynamic future in the face of multiple stressors acting individually and in combination: climate change; habitat change/loss; overfishing; invasive species; harmful algal blooms/eutrophication; and, chemical contaminants. Historic assessment and management approaches will be inadequate for addressing risks from climate change and other stressors. Wicked problems (non-linear, complex, competing risks and benefits, not easily solvable), will become increasingly common. We are facing irreversible changes to our planetary living conditions. Agreed protection goals and considering both the negatives (risks) and the positives (benefits) of all any and all actions are required, as is judicious and appropriate use of the Precautionary Principle. Researchers and managers need to focus on: determining tipping points (alternative stable points); maintaining ecosystem services; and, managing competing ecosystem services. Marine (and other) scientists are urged to focus their research on wicked problems to allow for informed decision-making on a planetary basis. Highlights: We face multiple stressors (physical, biological, chemical) acting individually and in combination. Global climate change affects habitat change, invasive species, algal blooms, and chemical toxicity. We must solve non-linear and complex wicked problems, with competing risks and benefits. Protection goals should be based on ecosystem services, not ecosystem health. Key research areas are tipping points, maintaining and managing competing ecosystem services.